Amorphous silica amendment to improve sandy soils’ hydraulic properties for sustained plant root access under drying conditions - Zarebanadkouki, Mohsen; Hosseini, Bahareh; Gerke, Horst H.; Schaller, Jörg (Frontiers in Environmental Science, 2022)
Climate scenarios predict more frequent and longer drought periods, potentially threatening agricultural yield. The water holding capacity of soils is crucial in controlling drought stress intensity for plants. Recently, amorphous silica (ASi) was suggested to increase soil water holding capacity and availability. The objective of this study was to explore the potential impact of Si application to soils on the retention and flow of water in soils and their consequence on plant access to water under soil drying conditions. Two sandy soils were mixed with varying contents (0, 1 and 5% g/g) of some selected ASi amendments. The soil water retention and soil hydraulic conductivity were determined using evaporation measurement device implemented in a commercial device called HYPROP. For both soils, an application of ASi at rates of 1 or 5% increased the water holding capacity significantly and soils treated with ASi maintained a higher hydraulic conductivity under soil drying conditions than the control soil. Simulation demonstrated that soils treated with ASi could longer sustain the transpirational demand of plants during a soil drying cycle. These first results confirm expected positive crop-growth effect of silica amendments on hydraulic properties of coarse-textured soils mainly by longer keeping up capillary flow during water extraction by plant roots.